Select winning stocks using technical analysis - Pistolese, Clifford (McGraw-Hill, 2007)
Selecting Winning Stocks Using Technical Analysis gives you practical techniques and exercises for quickly evaluating stocks using simple methods of technical analysis. Pistolese shows you how to conduct your own independent research to obtain objective data and identify investment opportunities, allowing you to shed broker fees and avoid conflicts of interest. He provides expert advice on tactical trading errors, controlling your emotions, and steering clear of the “herd mentality,” as well as how to:Locate companies with effective business models